2014
DOI: 10.1136/bmjopen-2013-004488
|View full text |Cite
|
Sign up to set email alerts
|

Facility versus unit level reporting of quality indicators in nursing homes when performance monitoring is the goal

Abstract: ObjectivesTo demonstrate the benefit of defining operational management units in nursing homes and computing quality indicators on these units as well as on the whole facility.DesignCalculation of adjusted Resident Assessment Instrument – Minimum Data Set 2.0 (RAI–MDS 2.0) quality indicators for: PRU05 (prevalence of residents with a stage 2–4 pressure ulcer), PAI0X (prevalence of residents with pain) and DRG01 (prevalence of residents receiving an antipsychotic with no diagnosis of psychosis), for quarterly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…This is consistent with a focus on the resident care unit in nursing homes as an important focus of quality of care improvement efforts. 61,62 Our models explain much higher levels of variance in CRU compared with IRU.…”
Section: Discussionmentioning
confidence: 94%
“…This is consistent with a focus on the resident care unit in nursing homes as an important focus of quality of care improvement efforts. 61,62 Our models explain much higher levels of variance in CRU compared with IRU.…”
Section: Discussionmentioning
confidence: 94%
“…Then, using logistic regression with improvement as the outcome we will investigate the effects of context (using ACT scales), best practice use, and staff characteristics on improvement. To this end we have developed a reliable classification system for individual control charts [49, 50]. …”
Section: Methodsmentioning
confidence: 99%
“…TREC is an ongoing research program and aims to create actionable performance data to improve performance at the clinical microsystem (care unit) level in nursing homes. The microsystem has rarely been targeted before in performance improvement trials and possesses unique features that make it key to leading care interventions and driving change in these settings [49, 50]. Our previous research demonstrated that members of the clinical microsystem are the best potential target to drive positive change in this field [49, 50].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations